A90 Where, when and who: Geographic, temporal and demographic patterns in cyclist road traffic casualties in West Yorkshire. Issue 2 (June 2015) - Lovelace, Robin; Roberts, Hannah; Kellar, Ian
Abstract: Background: Research indicates that overall, the health benefits of a modal shift to cycling greatly outweigh the risks. However, the extent of these benefits appears to vary across different contexts, in terms of both geography and demography. Within the UK cycling for everyday trips remains low, but we have seen an increase in general across the country despite a decrease in London. It is therefore important to understand the balance between the risks and benefits of cycling for different groups to effectively direct cycling policy. Few studies have focused on the geographical factors that affect cycling risk at a local level. Our approach was to examine the "where, when and who" in cycling road traffic casualties, which is appropriate for developing policies at a local scale. Methods: We analysed secondary data from the UK's STATS19 dataset, which reports road accident data from 2005 to 2012. We developed an equation to measure the underlying level of exposure and examined the spatial, temporal and demographic distribution of cyclist casualties within West Yorkshire. This region was selected due to its historically low cycling rates yet ambitious plans for improvements to its cycling infrastructure. A target of a 300% increase in the rate of cycling by 2026 has been set by the West Yorkshire Integrated Transport Authority, following investment from the Department of Transport. Results: West Yorkshire was found to be an unusually risky area for cyclists, with an estimated 53 deaths and 1372 serious injuries per billion kilometres cycled, based on census commuting statistics; this is roughly double the national average. This riskiness varies spatially and temporally, broadly aligning with previous literature. Cyclists were disproportionately at risk on high traffic roads, junctions and roundabouts. The proportion of traffic casualties involving cyclists has increased over time, in line with the national trend. An unexpected result was that cycling appears to be disproportionately risky for young people in West Yorkshire compared with young people nationally. Conclusions: This case study progresses our understanding that risk is context-specific and geographically and demographically variable. We have shown that risk to cyclists varies within West Yorkshire, which is more risky than national average for cyclists. We conclude that the identification of local hazardous areas using the methods presented can help to prioritise investment, and inform transport policy.